Analysis Of the Gender Wage Gap in Maluku Province Using Blinder-Oaxaca Decomposition - Aulia Sepnawati Putri; Ahmad Munir; Suparman Abdullah (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2022)
One of the eighth Sustainable Development Goal targets is to acomplish full and useful employment and decent work for all women and men, incorporating youth and people with incapacities, and equivalent compensation for work of equivalent worth. This study aims to discuss the gender wage gap between females and males in Maluku Province in 2020. One approach to analyzing household welfare could be measured through wages. Although there is an increase in LFPR, there is still a gender wage gap. Female wage inequality is an important concern today because females significantly contribute to economic development. Thus, it is necessary to conduct research related to factors that affect the wage inequality of female workers. This study uses secondary data from SAKERNAS (National Labor Force Survey) August 2020 with units of analysis as many as 4.293 households. Data analysis used was decomposition Blinder-Oaxaca to measure the gap and break down it into explained and unexplained gaps. The results showed that residence, marital status, education level, training participation, business sector, and Industry contribute to the gender wage gap in Maluku Province.